P531Cardiac resynchronization therapy in patients with permanent atrial fibrillation: insights from the HMEA database. (18th June 2020) - Rapacciuolo, A; Solimene, F; Iacopino, S; D"onofrio, A; Pisano", E; Zanotto, G; Curnis, A; Capucci, A; Senatore, G; Pignalberi, C; Maglia, G; Santamaria, M; et al.
Abstract: Funding Acknowledgements: This research did not receive any specific grant from funding agencies in the public, commercial, or not-for-profit sectors. Background/Introduction: The benefits of cardiac resynchronization therapy with defibrillator (CRT-D) in heart failure are well established. However, a gap of evidence is still present for patients with permanent atrial fibrillation (perm-AF) Purpose: To investigate outcomes of CRT-D patients with perm-AF in terms of appropriate shock for ventricular arrhythmia and all-cause mortality in a long-term time horizon. Methods: We used the Home Monitoring Expert Alliance (HMEA) database, a nationwide data repository of daily remote monitoring transmissions. The episodes with delivered shock were adjudicated by a board of 3 electrophysiologists. Results: Among 1226 CRT-D patients (mean age 71.2 ± 10.0 years; 75.5% males), 276 (22.5%) had perm-AF at device implantation. These patients had more frequently rate responsive function (19.7% vs 64.1%) and higher basic rate (median value 60 bpm vs 70 bpm) as compared to all other patients (p < 0.001). The CRT pacing percentage calculated over the first 2 months was slightly lower for perm-AF patients (median value 96.0% vs 98.8%, p < 0.001). At 5-year appropriate shock incidence was 34.2% (95% confidence interval [CI], 25.1%-45.3%) for perm-AF and 19.9% (15.6%-25.1%) for all other patients. All-cause mortality was 27.7% (17.7%-41.8%) for perm-AF and 15.6% (12.2%-19.9%) for all other patients. The age- and sex-adjusted hazard ratio between perm-AF and all other patients was 1.81 (95% CI: 1.25-2.64, p = 0.002) for appropriate shock and 0.92 (95% CI: 0.57-1.50, p = 0.748) for all-cause mortality. Conclusion: Although a higher incidence of appropriate shock, perm-AF at the time of CRT-D implantation was not associated with increased long-term mortality,